Development of the “Teamwork in Endoscopy Assessment Module for Endoscopic Non-Technical Skills” (TEAM-ENTS) behavioral marker system - Ravindran, Srivathsan; Cavilla, Rebecca; Ashrafian, Hutan; Haycock, Adam; Healey, Chris; Coleman, Mark; Archer, Steph; Darzi, Ara; Thomas-Gibson, Siwan; on behalf of the TEAM-ENTS working group; Ahmed, Omer; Almedia, Tiago; Anderson, John; Bartolome, Femma; Beales, Ian; Beintaris, Iosif; Berry, Philip; Boon, Claire; Borg-Bartolo, Simon; Brayford, Paula; Catelow, Jamie; Cheung, Vincent; Craig, Darren; Davies, Justin; Dhar, Anjan; Disney, Ben; Dodds, Phedra; El-Menabawey, Tareq; Follows, Rachael; Greig, Emma; Haslam, Neil; Hunt, Charlotte; Johnson, Gavin; Kelly, Christine; Loder, Daniel; Marshall, Sarah; Matharoo, Manmeet; McConnell, Susan; Mohan, Helen; Mountford, Chris; Murugananthan, Aravinth; Neilson, Laura; Ngu, Lena; Padua, Laurence; Panter, Simon; Patel, Krashna; Patel, Nisha; Polson, Rex; Powell, Sharon; Ratcliffe, Elizabeth; Raven, Beverley; Robbins, Joanne; Siau, Keith; Thomas, Rowena; Thorpe, Amelia; Thrupp, Nicola; Tolosa, Cynthia; Vance, Maggie; Verma, Ajay; Walker, Julie; Wells, Chris; Westwood, Clare; Williams, Ceri; Wood, Eleanor; Wood, Tracy; Wright, Karen; Wronska, Emilia (Endoscopy, 2022)
Background Non-technical skills (NTS) are integral to team performance and subsequent quality and safety of care. Behavioral marker systems (BMSs) are now increasingly used in healthcare to support the training and assessment of team NTS. Within gastrointestinal endoscopy, this is an area of novel research. The aims of this study were to define the core relevant NTS for endoscopy teams and develop a preliminary framework for a team-based BMS known as TEAM-ENTS (Teamwork in Endoscopy Assessment Module for Endoscopic Non-Technical Skills).Methods This study was conducted in two phases. In phase 1, a literature review of team-based BMSs was performed to inform an interview study of core endoscopy team members. Cognitive task analysis was used to break down the NTS relevant to endoscopy teams. Framework analysis generated the structure for the preliminary TEAM-ENTS framework. In phase 2, a modified Delphi process was undertaken to refine the items of the framework.Results Seven consultant endoscopists and six nurses were interviewed. The final coding framework consisted of 88 codes grouped into five overarching categories. In total, 58 participants were recruited to the Delphi panel. In the first round, nine elements and 37 behavioral descriptors did not meet consensus. Following item adjustment, merging and deletion, all remaining items met consensus thresholds after the second round. The refined TEAM-ENTS BMS consists of five categories, 16 elements, and 47 behavioral descriptors.Conclusions The refined TEAM-ENTS behavioral marker system was developed to reflect the core NTS relevant to endoscopy teams. Future studies will aim to fully validate this tool.